Penguatan Jiwa Kepemimpinan dan Kewirausahaan pada Pemuda melalui Pemberdayaan Karang Taruna dan UMKM di Pangkalan Jati, Cinere, Depok - Wahyuningtyas, Widayani; Sagala, Hairunnisa Br.; Intania, Nur; Wiati Gusti, Kharisma (KOMUNITA: Jurnal Pengabdian dan Pemberdayaan Masyarakat, 2025)
Pangkalan Jati in Cinere, Depok, is home to a vibrant youth population with potential reflected in youth organizations and growing localUMKMs. However, limited leadership capacity and entrepreneurial drive hinder the strategic role of youth in community development. This study explores the socio-economic dynamics of local youth and proposes an empowerment model focused on enhancing agency and independence. Using a qualitative approach, the research finds that while youth show strong enthusiasm and initiative, the lack of structured training, mentorship, and access to networks remains a significant barrier. Youth organizations and UMKMs can serve as platforms to foster leadership and entrepreneurship, especially when supported through collaboration among government, educational institutions, and civil society. Strengthening youth roles in this way supports the broader goals of the SDG’s, particularly in promoting empowered communities and inclusive economies.